Comprehensive analysis of the microbiome in Apis cerana honey highlights honey as a potential source for the isolation of beneficial bacterial strains - Pham T. Lanh; Bui T.T. Duong; Ha T. Thu; Nguyen T. Hoa; Dong Van Quyen (PeerJ, 2024)
Background Honey is a nutritious food made by bees from nectar and sweet deposits of flowering plants and has been used for centuries as a natural remedy for wound healing and other bacterial infections due to its antibacterial properties. Honey contains a diverse community of bacteria, especially probiotic bacteria, that greatly affect the health of bees and their consumers. Therefore, understanding the microorganisms in honey can help to ensure the quality of honey and lead to the identification of potential probiotic bacteria. Methods Herein, the bacteria community in honey produced by Apis cerana was investigated by applying the next-generation sequencing (NGS) method for the V3–V4 hypervariable regions of the bacterial 16S rRNA gene. In addition, lactic acid bacteria (LAB) in the honey sample were also isolated and screened for in vitro antimicrobial activity. Results The results showed that the microbiota of A. cerana honey consisted of two major bacterial phyla, Firmicutes (50%; Clostridia, 48.2%) and Proteobacteria (49%; Gammaproteobacteria, 47.7%). Among the 67 identified bacterial genera, the three most predominant genera were beneficial obligate anaerobic bacteria, Lachnospiraceae (48.14%), followed by Gilliamella (26.80%), and Enterobacter (10.16%). Remarkably, among the identified LAB, Lactobacillus kunkeei was found to be the most abundant species. Interestingly, the isolated L. kunkeei strains exhibited antimicrobial activity against some pathogenic bacteria in honeybees, including Klebsiella spp., Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa and Staphylococcus aureus. This underscores the potential candidacy of L. kunkeei for developing probiotics for medical use. Taken together, our results provided new insights into the microbiota community in the A. cerana honey in Hanoi, Vietnam, highlighting evidence that honey can be an unexplored source for isolating bacterial strains with potential probiotic applications in honeybees and humans.